2020
DOI: 10.4314/ahs.v20i4.5
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of seasonal influenza after the 2009 influenza pandemic in Africa: a systematic review

Abstract: Background: Influenza infection is a serious public health problem that causes an estimated 3 to 5 million cases and 250,000 deaths worldwide every year. The epidemiology of influenza is well-documented in high- and middle-income countries, however minimal effort had been made to understand the epidemiology, burden and seasonality of influenza in Africa. This study aims to assess the state of knowledge of seasonal influenza epidemiology in Africa and identify potential data gaps for policy formulation followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 224 publications
(425 reference statements)
0
3
0
Order By: Relevance
“…Vaccination period extends from October to December every year. Despite widespread policy recommendations on influenza vaccination, coverage is low in Tunisia, through the Eastern Mediterranean Region [ 18 ] and also in most African countries [ 19 ]. Among Tunisian health professionals, there was a low vaccination rate: only 15.3% were vaccinated against influenza in the 2018–2019 influenza season [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination period extends from October to December every year. Despite widespread policy recommendations on influenza vaccination, coverage is low in Tunisia, through the Eastern Mediterranean Region [ 18 ] and also in most African countries [ 19 ]. Among Tunisian health professionals, there was a low vaccination rate: only 15.3% were vaccinated against influenza in the 2018–2019 influenza season [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…These include A(H1N1)pdm2009, A(H3N2), A(H5N1) and influenza B viruses of the Victoria and Yamagata lineages [ 3 , 4 ]. Indeed, after the 2009 pandemic, only these four influenza viruses continued to circulate on a global scale [ 5 , 7 , 8 ]. Our work has shown that their influenza activity follows an annual and regional variation.…”
Section: Discussionmentioning
confidence: 99%
“…It is followed by a meta-analysis on seasonal flu that is highly relevant given that flu impacts the effects of Covid-19. 3 …”
mentioning
confidence: 99%